[Rezension von: Liss, Hanna, 1964-, Jüdische Bibelauslegung] - Kogman-Appel, Katrin 1958-; Liss, Hanna 1964- (2023)
Hanna Liss, Jüdische Bibelauslegung (UTB 5135. Jüdische Studien 4). Tübingen, Mohr Siebeck, 2020, XXVI, 538 Seiten
Gesehen am 31.07.2023
Keywords: Rezension